(untitled) (Gestão & Regionalidade, 2016)
This study took place in a company that changed the way of managing the production from Theory of Constraints (TOC) to lean manufacturing - Toyota Production System (STP) as a baseline to establish its competitive advantage. The company, one of the leaders of metal fittings industry, has low delivery lead-time of its products as the production objective. However, to maintain this objective, while using the TOC, the company needed to take advantage of high-volume stocks to prevent themselves from market and the process uncertainties. To establish its competitive advantage and reduce production costs, the company decided to deploy a lean manufacturing system. With the completion of the research, it was found that factors related to lean manufacturing elements were heavily related to the strength of their competitive advantage. This research is exploratory, descriptive and formatted along the lines of a single case study.